PENERAPAN METODE COMPERATIVE LEARNING UNTUK MENINGKATKAN KUALITAS HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS VIII SMP NEGERI 1 TUHEMBERUA - Remilianti Gulo; Kristin Mintaria Gea; Agnes Rostini Harefa (Peneliti.net, 2023)
This study aims to improve student learning outcomes in the Integrated Science subject at SMP Negeri 1 Tuhemberua. Natural Sciences (IPA) or IPA in a narrower sense is a scientific field which includes physics (physics) and biology (biology). The aim of learning science is to have knowledge learned through comparative learning methods and see how science lessons can improve student learning outcomes. The method used is classroom action research (CAR). Based on the research results, it was concluded that the learning outcomes of class VIII students of SMP Negeri 1 Tuhemberua were quite high after the cooperative learning method was applied. The results of cycle I to cycle II of this study showed that learning outcomes increased significantly. In cycle I, the average score of students in understanding the material was 70.57(68.57%), while in cycle II it increased to 87.71(85.71%).